Divergent Role of Programmed Death –Ligand 1 (PD-L1) in Renal Allografts with Antibody-Mediated Rejection (AMR). (July 2018) - Handan Ozdemir, B.; Akcay, Eda; Atilgan, Alev Ok; Borcek, Pelin; Tepeoglu, Merih; Polat, Aysegul Yucel; Deniz, Melis; Haberal, Mehmet
Abstract : Introduction: Interaction of PD-1 with PD-L1 has been shown to decrease T-cell proliferation and survival of T cells and is thought to exert inhibitory functions in experimental models of autoimmune diseases and transplantation. Despite the critical role of PD-L1 in T-cell biology and increasing knowledge of the function of PD-L1 in solid organ transplantation, its role in AMR is unknown. Although some studies demonstrated that PD-1/PD-L1 interaction is essential for the maintenance of graft tolerance, PD-1/PD-L1 interaction in renal allografts with AMR might exert different effects on immune cells. Since the vasculature is the first interface between the immune cells and the target graft, we aimed to understand the status of PD-1/PD-L1 interaction on endothelial cells and immune cells in peritubular capillaries (PTCs). Materials and Methods: Out of 110 cases, 68 had pure AMR (Group 1), and 42 had both AMR and ACR (Group 2). First indication biopsies reevaluated and the degree of the glomerular, PTC, interstitial leukocyte, macrophage, CD4, and CD8 positive lymphocytes graded. PTC and tubular HLA-DR expression studied. Loss of PTC-DR expression accepted as PTC destruction. The PD-1 and the PD-L1 expression on endothelial and inflammatory cells evaluated. The follow-up biopsies assessed for the development of interstitial fibrosis (IF). Results: Group 2 patients showed a higher incidence of endothelial and inflammatory cell PD-1/PD-L1 interaction compared to Group 1 (p<.01). The presence of both endothelial and inflammatory cell PD-1/PD-L1 interaction increase with increasing degree of interstitial, glomerular, PTC leukocyte, macrophage and CD8 positive lymphocytes (p<.01). A converse relationship found between PTC-DR expression and PD-1/PD-L1 interaction and positive association with tubular HLA-DR expression (p<.01). The development of IF was 48% and 13% in patients with endothelial PD-1/PD-L1 interaction and without endothelial PD-1/PD-L1interaction respectively (p<.001). Overall 1-, 3- and 5-year survival was 75%, 46 % and 35 % for patients with endothelial PD-1/PD-L1 interaction, while it was 92%, 76% and 69% for patients without endothelial PD-1/PD-L1 interaction (p<.001). Conclusion: Our results showed that high immunologic nature of AMR might form the basis for the unexpected functions of PD-L1 in renal allografts. Indeed, most experimental solid organ transplant studies showing a protective effect of the PD-1/PD-L1 pathway which they used transplant models with limited T-cell reactivity because of concomitant immunosuppression. We suggested thatthe inhibitory functions of the PD-1/PD-L1 pathway might not be capable under strong T-activation with high immunologic costimulator such as AMR.